an Pendampingan Pembuatan Produk Inovasi Olahan Ikan Asin pada Kelompok Nelayan RT 48 Kelurahan Manggar - Ugroseno Damara Prasadhana Handoyo; Shofa Agustina; Nazhiifah Oktavia Effendy; Ade Riyan Saputra; Suci Patiasari; Annisa Tahir Pagau (Abdimas Universal, 2024)
Innovation Development (PI) is an activity dedicated by STIE Madani Balikpapan students to Micro Small and Medium Enterprise (MSME) actors in one of the villages in Balikpapan city. The target of Micro Small and Medium Enterprises targeted by the group of 7 PI students of STIE Madani Balikpapan is the Fishermen Group in RT 48 Manggar Village, East Balikpapan District. The program was carried out with the cooperation of POKJA II Manggar Village, Family Welfare Empowerment Group and PT Pamapersada Nusantara Balikpapan. The objectives of Innovation Development activities are: 1) Helping with the processing of innovation products from salted fish; 2) Helping in the product packaging sticker design; 3) Helping in providing entrepreneurship knowledge through entrepreneurship seminar activities; and 4) Helping in the formation and inauguration of small micro enterprises groups and a new medium for the people of the RT 48 Fishery Group, Manggar Village. The result of Innovation Development in the RT 48 Manggar Village fishermen group is to form an MSME and produce an innovative product in the form of salted basreng fish, where salted fish is the catch of fishermen in RT 48 Manggar Village.